2013
DOI: 10.1097/mpg.0b013e31829d4f82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Holder Pasteurization and Frozen Storage on Macronutrients and Energy Content of Breast Milk

Abstract: Holder pasteurization decreased fat and energy content of human milk. Frozen storage at -20°C of pasteurized milk significantly reduced fat, lactose, and energy content of human milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 43 publications
(95 reference statements)
3
62
1
1
Order By: Relevance
“…We did not found any significant change in macronutrient values after pasteurization in SWB.A few studies have reported reduction in fat and energy after HoP. [4,5] García-Lara et al using MIRIS HMA showed a decrease in fat content following repeated freezing and thawing of pasteurized milk. [4] They emphasized that pasteurization itself is not related to reduction of nutrient values.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We did not found any significant change in macronutrient values after pasteurization in SWB.A few studies have reported reduction in fat and energy after HoP. [4,5] García-Lara et al using MIRIS HMA showed a decrease in fat content following repeated freezing and thawing of pasteurized milk. [4] They emphasized that pasteurization itself is not related to reduction of nutrient values.…”
Section: Discussionmentioning
confidence: 86%
“…[4,5] García-Lara et al using MIRIS HMA showed a decrease in fat content following repeated freezing and thawing of pasteurized milk. [4] They emphasized that pasteurization itself is not related to reduction of nutrient values. In our study using MIRIS, we did not find any difference in fat before and after pasteurization unlike García-Lara et al probably because our samples were analyzed immediately after samples were taken, frozen samples were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Energy is decreased in PDHM after pasteurization and storage compared with raw milk measurements. (19) PDHM bile salt-stimulated lipase is lost after the heating process (20) and can affect fat absorption and weight gain. To optimize human milk biologics and nutrients therefore provided to the infant, ongoing lactation support should prioritize mothers' own milk pumping.…”
Section: Differences Between Pdhm and Mommentioning
confidence: 99%
“…74 Both pasteurization and freezing have been shown to alter the nutritional properties of breast milk, including a significant reduction in fat, lactose, and energy content. 77 Because of the dire complications of CMV infection described above, the prevention of TT-CMV infection is essential when administering blood products to fetuses in utero, CMV-seronegative pregnant women, and premature VLBW infants. The effectiveness of CMV-seronegative blood products in the prevention of TT-CMV infection in neonates was demonstrated in an older landmark study by Yeager et al, which was conducted prior to the availability of LR products.…”
Section: Prevention Of Transfusion-transmitted Cytomegalovirusmentioning
confidence: 99%